Project Censored's state of the free press, 2024 : the top censored stories and media analysis of 2022-23 - Roth, Andrew Lee, 1968-; Huff, Mickey; MacLeod, Alan, 1977-; Stevens-Bollen, Anson (Censored Press ; Seven Stories Press, 2024)
"Highlighting the year's most significant independent journalism--including reports on toxic chemicals, climate disinformation, and union victories--Project Censored's State of the Free Press 2024 illuminates issues and raises voices that the establishment press have throttled."